Patterned growth of single-walled carbon nanotubes on silicon wafer for electronic devices by chemical vapor deposition process. - Le, Van Thang (Asean Engineering Journal)
The ability to controllably obtain ordered carbon nanotube architectures is important for fundamental characterizations and potential applications of electrical devices. Controlling the synthesis process applied chemical vapor deposition (CVD) has been an effective technique to order single-walled nanotubes (SWNTs) on patterned catalyst. In this paper, single-walled carbon nanotubes are synthesized by chemical vapor deposition of methane at positioned locations on a silicon substrate. This synthetic approach has allowed individual SWNT to be grown from appointed surface sites by catalyst patterning and has led to interconnecting SWNT electrical devices. The combined synthesis and microfabrication technique presented here enable the developing of many ohmically contacted nanotube devices that can be controlled the size. Base on TEM results, SWNTs are formed via an open-ended, base growth mechanism (VLS mechanism)